2016
DOI: 10.1167/iovs.15-18353
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immune Responses by Extracellular Vesicles From Retinal Pigment Epithelium

Abstract: PurposeExtracellular vesicles (EV), such as exosomes, are important mediators of intercellular communication and have been implicated in modulation of the immune system. We investigated if EV released from retinal pigment epithelium (RPE) modulate immune responses in vitro.MethodsExtracellular vesicles were isolated from ARPE-19 cultures stimulated or not with the inflammatory cytokines IL-1β, IFN-γ, and TNF-α. Isolated EV were characterized by nanoparticle flow and Western blot analyses. Retinal pigment epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 25 publications
1
50
1
Order By: Relevance
“…RPE cells and photoreceptors are sensitive to inflammatory stimulation [29,30], which may explain the differences in thicknesses between the physically active and inactive. Kim et al investigated these mechanisms in an experimental model, where they evaluated age-related changes on mice allocated either to regular aerobic training (treadmill training) or sedentary controls [31].…”
Section: Discussionmentioning
confidence: 99%
“…RPE cells and photoreceptors are sensitive to inflammatory stimulation [29,30], which may explain the differences in thicknesses between the physically active and inactive. Kim et al investigated these mechanisms in an experimental model, where they evaluated age-related changes on mice allocated either to regular aerobic training (treadmill training) or sedentary controls [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent in vitro study found that small EVs released from cultures of the spontaneously immortalized retinal pigmented epithelium (RPE) cell line ARPE-19, promoted an immunoregulatory phenotype in monocytes (Knickelbein et al, 2016). Interestingly, when ARPE-19 cultures were stimulated with inflammatory cytokines, they released EVs that induced monocyte death.…”
Section: Exosomes and Their Role In Immune Regulationmentioning
confidence: 99%
“…For example, mesenchymal stem cell-derived exosomes possess anti-inflammatory properties that may be applicable to inflammatory eye diseases (Blazquez et al, 2014; Zhang et al, 2014). As mentioned previously, RPE cells are thought to use exosomes to modulate local immune responses by killing monocytes (Knickelbein et al, 2016). Exosomes also appear to deliver anti-inflammatory drugs to microglial cells to suppress neuroinflammation (Zhuang et al, 2011) or αB-crystallin to the neural retina, which could act as neuroprotection to photoreceptors (Sreekumar et al, 2010).…”
Section: Exosomes As Therapeutic Agentsmentioning
confidence: 99%
“…RPE cells have been revealed to have immunosuppressive properties, including induction of Tregs and inhibition of Th17 and Th22 cell differentiation [91]. Knickelbein et al reported that exosomes released by both resting and cytokine-stimulated RPE cells suppressed the proliferation of T lymphocytes isolated from the peripheral blood of noninfectious uveitis patients, and these nanosized vesicles could also regulate human monocyte phenotype and viability [59]. The above results indicate that exosome secretion may be a crucial mechanism for RPE cells to perform their immunoregulatory effects.…”
Section: Autoimmune Uveitismentioning
confidence: 99%